Adaptive classification under computational budget constraints using sequential data gathering. (September 2016) - van der Herten, Joachim; Couckuyt, Ivo; Deschrijver, Dirk; Dhaene, Tom
Highlights: The extension of the SUMO-Toolbox for classification is presented. State-of-the-art tool for modeling and optimization of budget-constrained problems. Includes the Neighborhood-Voronoi method for sequential sampling. Illustrative examples, including complex expensive constrained optimization. Abstract: Classification algorithms often handle large amounts of labeled data. When a label is the result of a very expensive computer experiment (in terms of computational time), sequential selection of samples can be used to limit the overall cost of acquiring the labeled data. This paper outlines the concept of sequential design for classification, and the extension of an existing state-of-the-art research platform for surrogate modeling to handle classification problems with sequential design. The capabilities of the platform are illustrated on a number of use cases including real-world applications such as an ElectroMagnetic Compatibility (EMC) and a Computational Fluid Dynamics (CFD) problem. The CFD problem also illustrates how classification can be used together with regression techniques to solve multi-objective constrained optimization problems of complex systems.